Integrating Greenhouse Cherry Tomato Production with Biofloc Tilapia Production - Jeremy M. Pickens; Jason J. Danaher; Jeff L. Sibley; Jesse A. Chappell; Terry R. Hanson (Horticulturae, 2020)
Integration of intensive aquaculture systems with greenhouse plant production has been shown to improve aquaculture water quality conditions and improve plant nutrient use efficiency. The majority of the focus of integrated systems has involved raft culture or true hydroponics. Little work has been done on soilless culture utilizing drip irrigation. This study investigates the feasibility of integrating biofloc Nile tilapia (Oreochromis niloticus) production with greenhouse cherry tomato production (Solanum lycopersicum var. cerasiforme). Nile tilapia (157 g/fish) were stocked at 40 fish/m3 and grown for 149 days. The cherry tomato cvs. “Favorita” and “Goldita” were grown with aquaculture effluent (AE) waste and compared to plants grown with conventional fertilizer (CF) in soilless culture. Plants were grown for 157 days. Few differences in yield occurred between treatments until fish harvest (117 DAT). Post fish harvest, there was an 18.4% difference in total yield between CF and AE at crop termination for “Favorita”. Differences in yield between AE and CF were observed for “Goldita” at fish harvest (117 DAT) and crop termination (157 DAT). Results from this study suggest the potential for successful integration of cherry tomato grown in a substrate-based system with AE from a tilapia biofloc production system.